2020
DOI: 10.1021/acssuschemeng.0c03314
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Production of Sustainable Hydrocarbon Fuels from CO2 Co-electrolysis in Eutectic Molten Melts

Abstract: Due to the heavy reliance of people on the limited fossil fuel as energy resources, global warming has increased to severe levels due to huge CO2 emission into the atmosphere. To mitigate this situation, a green method is presented here for the conversion of CO2/H2O into sustainable hydrocarbon fuels via electrolysis in eutectic molten salts ((KCl-LiCl; 41:59 mol%), (LiOH-NaOH; 27:73 mol%), (KOH-NaOH; 50:50 mol%), (Li2CO3-Na2CO3-K2CO3; 43.5:31.5:25 mol%)) at the conditions of 1.5-2 V and 225-475 o C depending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(42 citation statements)
references
References 62 publications
(175 reference statements)
1
39
0
Order By: Relevance
“…6 revealed that the products in the case of titanium cathodic materials were more specific as found in higher molecular weight, long-chain hydrocarbons and thus offer a higher enthalpy of combustion to produce energy or higher heat values. These findings correlate with the literature 9 .…”
Section: Optimization Of Electrodessupporting
confidence: 93%
See 1 more Smart Citation
“…6 revealed that the products in the case of titanium cathodic materials were more specific as found in higher molecular weight, long-chain hydrocarbons and thus offer a higher enthalpy of combustion to produce energy or higher heat values. These findings correlate with the literature 9 .…”
Section: Optimization Of Electrodessupporting
confidence: 93%
“…..The electrolysis is considered an effective method for the production of hydrocarbon fuel from CO2 and H2O. The aqueous electrolysis at low temperatures (<100 o C) was employed by scientists 9 , whereas suitable catalyst to reduce energy consumption and increase product selectivity is necessary 10 . Besides the low solubility of CO2 in the medium, slow kinetics, low productivity due to unseparated products limits its future use 11 .…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 emissions must be curtailed to mitigate global warming and enhance sustainable development ( Lelieveld et al, 2019 ). This strategy hinges on alternative energy technologies, which include: solar and wind power ( Qazi et al, 2019 ); sustainable hydrocarbon fuel production from CO 2 ( Al-Juboori et al, 2020b ); hydrogen fuel cells ( Al-Shara et al, 2019 ); and biofuels ( Razzaq et al, 2020 ). Additionally, carbon capture and sequestration techniques such as post-combustion CO 2 capture using fast adsorbents derived from biomass ( Sher et al, 2020 ) can reduce CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CO 2 and climate change are important issues for power plants. Some new concepts have been introduced: selective configuration of exhaust gas recirculation systems to reduce CO 2 emission in the natural gas combined-cycle power plants [28], and CO 2 capture and reduction via different methods [29,30].…”
Section: Introductionmentioning
confidence: 99%